INCREASED INCIDENCE OF INJURIES IN THE SÃO PAULO SOCCER CHAMPIONSHIP POST-PANDEMIC - Alexandre Moreira Sales; Paulo Henrique Schmidt Lara; Nathalia Bofill Burger; Raphael Ribeiro Moreira; Moisés Cohen; Gustavo Gonçalves Arliani (Acta Ortopédica Brasileira)
ABSTRACT Objective: Soccer shows a high incidence of injuries and its cause is multifactorial. The impacts of the coronavirus pandemic are unknown. This study aims to evaluate the incidence of injuries in the 2023 Campeonato Paulista de Futebol (São Paulo Soccer Championship) and compare it to the championships prior to the pandemic. Methods: This study was conducted by collecting data on injuries among players in the A1 Series of the 2023 São Paulo Soccer Championship. Injuries were recorded by each team’s medical staff via an online questionnaire. The variables included: Type of Field, Weather, Temperature, Distance, Home Advantage, Age, Type and Location of Injury. The primary outcome is to evaluate the incidence of injuries, and the secondary outcomes are to analyze the relationship between the described variables, the observed incidence, and the comparison of data obtained from 2016 to 2019. Results: In 2023, 76 injuries were recorded, an incidence of 22.1 injuries/1,000h. Muscle injuries (46.1%) and sprains (18.4%) were the most common. From 2016 to 2019, there was a decrease in the incidence of injuries per 1,000h, respectively: 24.2; 17.6; 14 and 10.5. Conclusion: the incidence in 2023 was 22.1 injuries/1,000h, which points to an increase compared to the pre-pandemic period. Level of Evidence II, Comparative Prospective Study